Cluster mass calibration at high redshift: HST weak lensing analysis of 13 distant galaxy clusters from the South Pole Telescope Sunyaev–Zel'dovich Survey. Issue 2 (14th October 2017) - Schrabback, T; Applegate, D; Dietrich, J P; Hoekstra, H; Bocquet, S; Gonzalez, A H; von der Linden, A; McDonald, M; Morrison, C B; Raihan, S F; Allen, S W; Bayliss, M; et al.
Abstract: We present an HST /Advanced Camera for Surveys (ACS) weak gravitational lensing analysis of 13 massive high-redshift ( z median = 0.88) galaxy clusters discovered in the South Pole Telescope (SPT) Sunyaev–Zel'dovich Survey. This study is part of a larger campaign that aims to robustly calibrate mass–observable scaling relations over a wide range in redshift to enable improved cosmological constraints from the SPT cluster sample. We introduce new strategies to ensure that systematics in the lensing analysis do not degrade constraints on cluster scaling relations significantly. First, we efficiently remove cluster members from the source sample by selecting very blue galaxies in V − I colour. Our estimate of the source redshift distribution is based on Cosmic Assembly Near-infrared Deep Extragalactic Legacy Survey (CANDELS) data, where we carefully mimic the source selection criteria of the cluster fields. We apply a statistical correction for systematic photometric redshift errors as derived from Hubble Ultra Deep Field data and verified through spatial cross-correlations. We account for the impact of lensing magnification on the source redshift distribution, finding that this is particularly relevant for shallower surveys. Finally, we account for biases in the mass modelling caused by miscentring and uncertainties in the concentration–mass relation using simulations. In combination with temperature estimates from Chandra we constrain the normalization of the mass–temperature scaling relation ln ( E ( z ) M 500c /10 14 M⊙ ) = A + 1.5ln ( kT /7.2 keV) to $A=1.81^{+0.24}_{-0.14}(stat.)\, {± }\, 0.09(sys.)$, consistent with self-similar redshift evolution when compared to lower redshift samples. Additionally, the lensing data constrain the average concentration of the clusters to $c_200c=5.6^{+3.7}_{-1.8}$ .